The Nucleoid-Associated Protein GapR Uses Conserved Structural Elements To Oligomerize and Bind DNA - Rogério F. Lourenço (American Society for Microbiology, 2020)
ABSTRACT Nucleoid-associated proteins (NAPs) are DNA binding proteins critical for the organization and function of the bacterial chromosome. A newly discovered NAP in Caulobacter crescentus, GapR, is thought to facilitate the movement of the replication and transcription machines along the chromosome by stimulating type II topoisomerases to remove positive supercoiling. Here, utilizing genetic, biochemical, and biophysical studies of GapR in light of a recently published DNA-bound crystal structure of GapR, we identified the structural elements involved in oligomerization and DNA binding. Moreover, we show that GapR is maintained as a tetramer upon its dissociation from DNA and that tetrameric GapR is capable of binding DNA molecules in vitro. Analysis of protein chimeras revealed that two helices of GapR are functionally conserved in H-NS, demonstrating that two evolutionarily distant NAPs with distinct mechanisms of action utilize conserved structural elements to oligomerize and bind DNA. IMPORTANCE Bacteria organize their genetic material in a structure called the nucleoid, which needs to be compact to fit inside the cell and, at the same time, dynamic to allow high rates of replication and transcription. Nucleoid-associated proteins (NAPs) play a pivotal role in this process, so their detailed characterization is crucial for our understanding of DNA organization into bacterial cells. Even though NAPs affect DNA-related processes differently, all of them have to oligomerize and bind DNA for their function. The significance of this study is the identification of structural elements involved in the oligomerization and DNA binding of a newly discovered NAP in C. crescentus and the demonstration that structural elements are conserved in evolutionarily distant and functionally distinct NAPs.